2014
DOI: 10.3109/00016357.2014.913307
|View full text |Cite
|
Sign up to set email alerts
|

Addition of benzalkonium chloride to self-adhesive resin-cements: some clinically relevant properties

Abstract: BAC addition of up to 1% seems to be acceptable considering the properties tested. Clinical significance. Incorporation of benzalkonium chloride to self-adhesive resin luting cements during the mixing procedure does not significantly affect the degree of conversion or flexural strength of the luting agent and may be a good option to improve the durability of adhesive interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…AH 15 Plus is mostly composed of an organic matrix with the radiopacifiers contributing to the inorganic crystalline phases. 10 Chemical changes could be observed with the FT-IR that showed high peaks in amines and chlorides (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AH 15 Plus is mostly composed of an organic matrix with the radiopacifiers contributing to the inorganic crystalline phases. 10 Chemical changes could be observed with the FT-IR that showed high peaks in amines and chlorides (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 BC has been included in different dental restorative materials such as adhesives, glass ionomer cements and resin composites to concentrations up to 5% conferring it with beneficial antibacterial properties and long lasting effects due to its capacity to inhibit the proteases. [14][15][16] Besides, when incorporated in a resin composite the shear bond strength increases and release of BC was observed over time. 17 Using the agar diffusion test, AH Plus when mixed with 2% BC exhibited better antimicrobial effect.…”
Section: Introductionmentioning
confidence: 94%
“…The strength of polymerized resinous luting cement depends on the composition, polymerization reaction, and extent of the polymer network. The polymerization characteristics of SACs have been previously investigated in studies of their double-bond conversion 24) , surface hardness 25) , flexural strength and elastic modulus 26) , ion release 27) , and rheology 28) . However, quantification of the extent of polymerization reactions at a given point has faced difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…: -implants 97) , pulp capping materials 98) , Transbond XT 99) , pit and fissure sealing 100) , cavity disinfectant 101) , resin cement 102), zinc phosphate cement, and zinc polycarboxylate cement 103) . These studies have shown that QACs possess antimicrobial activities against bacteria and fungi including S. mutans, L. acidophilus, C. albicans, E. faecalis ect.…”
Section: Discussionmentioning
confidence: 99%